THE IMPLEMENTATION INCLUSIVE EDUCATION: IMPLICATION FOR CHILDREN WITH SPECIAL NEEDS IN TAMANSARI ELEMENTARY SCHOOL IN YOGYAKARTA - Rofiah, Nurul Hidayati; Sudiraharja, Dara; Ediyanto, Ediyanto (International Journal of Educational Management and Innovation, 2020)
Many children with special needs do not have access to education. The number of children with special needs who have to attend primary school is still very minimal. Most schools only provide regular education, while students are ordinary children who do not need special needs in their education. This study aims to describe the model of implementing inclusive education in Tamansari Elementary Schools and find problems in implementing inclusive education. The research method is qualitative interactive. Data collection use interviews, observation, and documentation methods. Data analysis uses interactive analysis. The results showed that Tamansari Elementary School used a full class model. Identification and assessment are carried out before accepting students with special needs. This is done to gather information before preparing a learning program for students with special needs according to their learning needs. The curriculum is modified to suit the children’s needs. The special teacher comes from a special school near the location. Supporting factors are the acceptance of children with special needs, local government support in the implementation of inclusive education, while obstacle factors in the application of inclusive education are limited special teachers and limited infrastructure.